2016 11th System of Systems Engineering Conference (SoSE) 2016
DOI: 10.1109/sysose.2016.7542941
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing safety of transport by road by on-line monitoring of driver emotions

Abstract: Driving while fatigued is dangerous and may result in car accidents. Moreover, adding technology to assist driving can distract the driver. In this work, we present a noninvasive and non-distracting method for monitoring driver emotions and fatigue. To the best of our knowledge, no scientifically agreed definition of emotions exists, as a physical state to be monitored. Emotion recognition is defined as measuring observations of motor system behavior that correspond with high probability to an underlying emoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 3 publications
0
29
0
Order By: Relevance
“…Emotion recognition has been applied in many areas such as safe driving [ 1 ], health care especially mental health monitoring [ 2 ], social security [ 3 ], and so on. In general, emotion recognition methods could be classified into two major categories.…”
Section: Introductionmentioning
confidence: 99%
“…Emotion recognition has been applied in many areas such as safe driving [ 1 ], health care especially mental health monitoring [ 2 ], social security [ 3 ], and so on. In general, emotion recognition methods could be classified into two major categories.…”
Section: Introductionmentioning
confidence: 99%
“…Driver stress can be caused by many stressors such as: mood changes, biorhythm, fatigue, boredom, disease, drugs, traffic (e.g. busy city [26]), weather, night driving, problems in job/family, workload [21], [27], [9]. In spite of the possibility to introduce a list of the most frequent stressors in drivers or according to the classical theories [28], a high inter-individual variability is typical for the start of the stress reaction [29], [13].…”
Section: Introductionmentioning
confidence: 99%
“…From the methodological point of view, the approach adopted in this study can be summarized by the diagram reported in Figure 1. It should be underlined that investigation of the driver's psychophysical state was performed in several previous studies [22][23][24][25][26][27][28][29][30][31]. The added value of this paper is an investigation into how this aspect influences driving activity, in particular, the probability that high levels of stress or relaxation could impact on-road safety issues, supporting a preventive approach for road safety analysis.…”
Section: Methodsmentioning
confidence: 87%